2020
DOI: 10.3390/s20041214
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Respiratory Pathologies Using Convolutional Neural Networks and Variational Autoencoders for Unbalancing Data

Abstract: The aim of this paper was the detection of pathologies through respiratory sounds. The ICBHI (International Conference on Biomedical and Health Informatics) Benchmark was used. This dataset is composed of 920 sounds of which 810 are of chronic diseases, 75 of non-chronic diseases and only 35 of healthy individuals. As more than 88% of the samples of the dataset are from the same class (Chronic), the use of a Variational Convolutional Autoencoder was proposed to generate new labeled data and other well known ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 26 publications
0
59
0
Order By: Relevance
“…( 2020 ) 126 6898 4: Normal, crackles, wheezes crackles+wheezes Spectrograms CNN Accuracy: 71.15 Sensitivity: 61.00 Specificity: 86.00 García-Ordás et al. ( 2020 ) 126 920 6: Normal, asthma, pneumonia BRON, COPD, respiratory tract infection Spectrograms CNN Accuracy: N/A Sensitivity: 98.81 Specificity: 98.61 This study 213 1,483 6: Normal, asthma, pneumonia BRON, COPD. heart failure Spatial and temporal (CNN + BDLSTM) CNN + BDLSTM Accuracy: 99.62 Sensitivity: 98.43 Specificity: 99.69 …”
Section: Resultsmentioning
confidence: 87%
“…( 2020 ) 126 6898 4: Normal, crackles, wheezes crackles+wheezes Spectrograms CNN Accuracy: 71.15 Sensitivity: 61.00 Specificity: 86.00 García-Ordás et al. ( 2020 ) 126 920 6: Normal, asthma, pneumonia BRON, COPD, respiratory tract infection Spectrograms CNN Accuracy: N/A Sensitivity: 98.81 Specificity: 98.61 This study 213 1,483 6: Normal, asthma, pneumonia BRON, COPD. heart failure Spatial and temporal (CNN + BDLSTM) CNN + BDLSTM Accuracy: 99.62 Sensitivity: 98.43 Specificity: 99.69 …”
Section: Resultsmentioning
confidence: 87%
“…The proposed technique has provided an efficient approach with outstanding classification accuracy. It has outperformed as compared to existing techniques on other multiple pulmonic pathologies from LS analysis due to its simple statistical features, low computation, and accuracy [ 6 , 7 , 12 , 20 , 22 , 24 , 25 , 28 , 29 ]. The performance analysis of the proposed diagnostic technique with existing pulmonic pathologies methods is shown in Table 9 .…”
Section: Resultsmentioning
confidence: 99%
“…But the research work only focused to classify the adventitious sounds found in various pulmonic illnesses [ 28 ]. In another research, a novel approach called variational convolutional autoencoder is presented for unbalanced data and implemented on the same database [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the near future, electronic stethoscopes with automatic machine learning based classification and interpretation of lung sounds might be helpful in this respect. 30 Differentiation between coarse and fine and between early and late crackles can probably be taken into account in future devices and mHealth solutions, being thus more easily integrated in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%